How do you solve this 6/5(5-4g)=-18


Notice: Undefined variable: position6 in /home/domains2/public_html/painphr.com/show.php on line 143

Guide :

How do you solve this 6/5(5-4g)=-18

the answer is g=5

Research, Knowledge and Information :



Notice: Undefined variable: go_page in /home/domains2/public_html/painphr.com/show.php on line 211

5g+18-7g+4g=8 - solution - Get Easy Solution


Simple and best practice solution for 5g+18-7g+4g=8 equation. Check how easy it is, ... -2g + 4g = 2g 18 + 2g = 8 Solving 18 + 2g = 8 Solving for variable 'g'.
Read More At : www.geteasysolution.com...

6/5(5-4g)=-18 - Get Easy Solution


Simple and best practice solution for 6/5(5-4g)=-18 equation. Check how easy it is, ... SOLVE: Solution for 6/5(5-4g)=-18 equation: 6/5(5-4g)=-18
Read More At : www.geteasysolution.com...

6/5(5-4g)=-18 - OpenStudy


... =-18what's in the numerator on the left?. \[6/5(5-4g)=-18\] \[5-4g=-18\frac{5}{6}=-15\] \[-4g=-20\] \[g=5 ... Learn how to solve problems with step-by-step ...
Read More At : openstudy.com...

Solve Math Problems


... or solving a real-life problem. From finding the average, to converting units, ... What Do You Need Help With? Statistics Calculator; Calculus Calculator;
Read More At : solvemathproblems.org...

How do you solve 6- 5+ n \geq 18? | Socratic


... 6-5+n>=18 Let's put it into words Six minus five plus n is greater than or equal to eighteen. ... How do you solve #y=|x|# and #y=x+2# using ...
Read More At : socratic.org...

Solving an Equation - Avvanta


Solving an Equation ... X = 6: Because 3 times 6 = 18: X/4 = 5: If you divide my number by 4, you get 5. ... and how you would solve them: Equation
Read More At : home.avvanta.com...

5 Ways to Solve for X - wikiHow - How to do anything


How to Solve for X. There are a number of ways to solve for x, ...
Read More At : www.wikihow.com...

Home | MIT - Solve


If you have a solution to one of these big global challenges, ... Become part of Solve’s global community and enjoy these member benefits: Access to Solve events;
Read More At : solve.mit.edu...

Solving One-Step Linear Equations - Purplemath


Solving One-Step Linear Equations (page 2 of 4) Sections: One ... Solve x / 5 = –6; Since the x is divided by 5, I'll want to multiply both sides by 5:
Read More At : www.purplemath.com...

6^2 ÷ 2(3) + 4 = ? The Correct Answer - YouTube


Apr 28, 2015 · 6^2 ÷ 2(3) + 4 = ? The Correct Answer ... You may also like my video on 6 ... Can You Solve The Viral 1 + 4 = 5 Puzzle?

Suggested Questions And Answer :



Notice: Undefined variable: position4 in /home/domains2/public_html/painphr.com/show.php on line 277

how to solve for x with fractions

Simplifying x3 + 3x2 + -4x = 0 Reorder the terms: -4x + 3x2 + x3 = 0 Solving -4x + 3x2 + x3 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), 'x'. x(-4 + 3x + x2) = 0 Factor a trinomial. x((-4 + -1x)(1 + -1x)) = 0 Subproblem 1 Set the factor 'x' equal to zero an
Read More: ...

Notice: Undefined variable: position4 in /home/domains2/public_html/painphr.com/show.php on line 277

How do I solve y=-x-4

How do I solve y=-x-4 I need to be able to plot these points on a graph but i don't know how to solve the problem.   make an x & y axis. ( like a cross one line goes vertical an the other horizontal) put equal dimention for x & y line From center line moving
Read More: ...

Notice: Undefined variable: position4 in /home/domains2/public_html/painphr.com/show.php on line 277

x - z = -3, y + z = 9, -2x + 3y +5z = 33

Problem: x - z = -3, y + z = 9, -2x + 3y +5z = 33 1) x - z = -3 2) y + z = 9 3) -2x + 3y + 5z = 33 Add equation 2 to equation 1.      x     - z = -3 +(    y + z =  9) ------------------   x + y     = 6 4)
Read More: ...

Notice: Undefined variable: position4 in /home/domains2/public_html/painphr.com/show.php on line 277

(13-3)x5=50

Simplifying x + 2 = 3x + -1x2 + 5 Reorder the terms: 2 + x = 3x + -1x2 + 5 Reorder the terms: 2 + x = 5 + 3x + -1x2 Solving 2 + x = 5 + 3x + -1x2 Solving for variable 'x'. Reorder the terms: 2 + -5 + x + -3x + x2 = 5 + 3x + -1x2 + -5 + -3x + x2 Combine like terms: 2 + -5 = -3 -3 + x + -3x + x2
Read More: ...

Notice: Undefined variable: position4 in /home/domains2/public_html/painphr.com/show.php on line 277

(8x)[(2x)^-2=8

Simplifying 8x = 2x2 + 8 Reorder the terms: 8x = 8 + 2x2 Solving 8x = 8 + 2x2 Solving for variable 'x'. Reorder the terms: -8 + 8x + -2x2 = 8 + 2x2 + -8 + -2x2 Reorder the terms: -8 + 8x + -2x2 = 8 + -8 + 2x2 + -2x2 Combine like terms: 8 + -8 = 0 -8 + 8x + -2x2 = 0 + 2x2 + -2x2 -8 + 8x + -2x2
Read More: ...

Notice: Undefined variable: position4 in /home/domains2/public_html/painphr.com/show.php on line 277

Whats 3x-2 over 9 equals 25 over 3x-2?

I will give you an example for this question. This might be able to help you. Simplifying 3x2 + 25x = 18 Reorder the terms: 25x + 3x2 = 18 Solving 25x + 3x2 = 18 Solving for variable 'x'. Reorder the terms: -18 + 25x + 3x2 = 18 + -18 Combine like terms: 18 + -18 = 0 -18 + 25x + 3x2 = 0 Fac
Read More: ...

Notice: Undefined variable: position4 in /home/domains2/public_html/painphr.com/show.php on line 277

3x + 6y – 6z = 9 2x – 5y + 4z = 6 -x +16y + 14z = -3 what is the answer

3x + 6y – 6z = 9 2x – 5y + 4z = 6 -x +16y + 14z = -3 what is the answer how do you solve it and what are the answers ? 1)  3x + 6y – 6z = 9 2)  2x – 5y + 4z = 6 3)  -x +16y + 14z = -3 The first objective is to eliminate z so we can solve for x and y. It's a multi-step proces
Read More: ...

Notice: Undefined variable: position4 in /home/domains2/public_html/painphr.com/show.php on line 277

what is general solution for dw/dt = 7w+6y-10z

what is general solution for dw/dt = 7w+6y-10z dx/dt= 3w + x +3y-5z dy/dt= 5w+2x+11y-14z dz/dt=5w+2x+8y-11z Represent the coupled differential equations in matrix form. X = Av Where X is the column vector [w’ x’ y’ z’] and x’ = dx/dt, etc. And A is the component mat
Read More: ...

Notice: Undefined variable: position4 in /home/domains2/public_html/painphr.com/show.php on line 277

solve for x: 3x^2-5x+2=0

Problem: solve for x: 3x^2-5x+2=0 solve for x: 3x^2-5x+2=0 (3x - 2)(x - 1) = 0    set each factor to zero and solve for x (3x - 2) = 0 3x = 2 x = 2/3 (x - 1) = 0 x = 1 Check. 3x^2 - 5x + 2 = 0 3(2/3)^2 - 5(2/3) + 2 = 0 3(4/9) - 10/3 + 2 = 0 4/3 - 10/3 + 2 = 0 -6
Read More: ...

Notice: Undefined variable: position4 in /home/domains2/public_html/painphr.com/show.php on line 277

solve for x when (.182+x)/(.106-2x)=3.24

solve for x when (.182+x)/(.106-2x)=3.24 Im trying to solve for x its for a chemistry equation but i need to solve for x using the quadratic equation and i dont know which equals a b and c to find x. ************************** You can't solve this with the quadratic formula, because there is no x^2
Read More: ...

Tips for a great answer:

- Provide details, support with references or personal experience .
- If you need clarification, ask it in the comment box .
- It's 100% free, no registration required.
next Question || Previos Question

Notice: Undefined variable: position5 in /home/domains2/public_html/painphr.com/show.php on line 357
  • Start your question with What, Why, How, When, etc. and end with a "?"
  • Be clear and specific
  • Use proper spelling and grammar
all rights reserved to the respective owners || www.painphr.com || Terms of Use || Contact || Privacy Policy
Load time: 0.0965 seconds